IMPLEMENTASI ETNOMATEMATIKA DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Indri Siti Badi'ah; Dwi Retno Agustiani; Dede Desi Nurdania; Dini Septriani; Dinar Luqiana Nisrina Herawati; Nurul Khotimah (STKIP Subang, 2026)
Ethnomathematics is a learning approach that integrates local culture with mathematical concepts, making learning more contextual and meaningful. This study aims to examine the implementation of ethnomathematics in elementary school mathematics education through a Systematic Literature Review (SLR) method. The review was conducted following the PRISMA 2020 guidelines, with data sources obtained from Google Scholar and Scopus covering publications from 2017 to 2025. From a total of 512 articles identified through the search process, 15 articles met the inclusion criteria and were selected for analysis. The findings indicate that ethnomathematics has been implemented through the integration of local culture, traditional games, batik, traditional dances, cultural artifacts, and culture-based learning media. These implementations have been shown to enhance students’ understanding of mathematical concepts, learning outcomes, problem-solving skills, learning motivation, and appreciation of local culture. Therefore, ethnomathematics has significant potential as an effective and innovative approach to elementary school mathematics education.